Environmental cost analysis and reporting to measure environmental performance in realizing eco-efficiency at PT Industri Kereta Api (Persero) - Basuki Basuki; Riasty Dewi Irwanda (Asian Journal of Accounting Research, 2018)
The purpose of this paper is to simulate the environmental cost reports preparation used to measure environmental performance in realizing eco-efficiency.This research uses a descriptive case study by using environmental cost detail data from 2011, 2012, 2013 and 2014. The research object is PT Industri Kereta Api (Persero) located in Madiun, East Java.The result of the research shows that PT INKA (Persero) has not specifically made environmental cost report. It is found that the percentage of total environmental cost to operational cost tends to increase; the cost which gives the biggest distribution of total environmental cost is the prevention cost. By 2014, the effect of environmental costs on operating costs tended to decrease and during 2012–2014 PT INKA successfully maintained the blue star PROPER and the absence of environmental pollution reports.PT INKA’s environmental performance is still well controlled and since its inception in 2014 PT INKA has succeeded in realizing the concept of eco-efficiency.